The 2nd International Research Conference on Sustainable Energy, Engineering, Materials and Environment 2018
DOI: 10.3390/proceedings2231467
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Drying of Brewers’ Spent Grain

Abstract: Brewing industry generates a main residue, brewers’ spent grain (BSG), which has good properties both for use in animal consumption and for thermal use, but contains a very high content of moisture (20–25% dry matter content), so that its elimination or treatment should be immediate, since it can cause degeneration problems of the product. Currently, brewers often supply this material at low cost for use as livestock feed. This solution is not efficiently carried out without reporting too much benefit to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
(13 reference statements)
2
13
0
1
Order By: Relevance
“…The use of an indirect method is tempting, especially that it does not require to check the mass of the whole batch after HTC, which could be especially cumbersome and impractical for future industrial-scale installations. However, more research is needed to confirm the suitability of this method for assessment of the productivity of the HTC process in general, as well as specifically for its use for the spent grain.Drying of BSG was investigated by Arranz et al [50]. The study showed that significant drying time, exceeding 100 min is required to remove 80% of the original moisture [50].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The use of an indirect method is tempting, especially that it does not require to check the mass of the whole batch after HTC, which could be especially cumbersome and impractical for future industrial-scale installations. However, more research is needed to confirm the suitability of this method for assessment of the productivity of the HTC process in general, as well as specifically for its use for the spent grain.Drying of BSG was investigated by Arranz et al [50]. The study showed that significant drying time, exceeding 100 min is required to remove 80% of the original moisture [50].…”
mentioning
confidence: 99%
“…However, more research is needed to confirm the suitability of this method for assessment of the productivity of the HTC process in general, as well as specifically for its use for the spent grain.Drying of BSG was investigated by Arranz et al [50]. The study showed that significant drying time, exceeding 100 min is required to remove 80% of the original moisture [50]. Obtained effective diffusities were significantly lower than those reported for olive pomace, making BSG a much more challenging material in terms of its drying [50].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Содержание воды в пивной дробине составляет 75-85%, а сухой остаток содержит порядка 6,6% белковых веществ, 1,7% жира и 9,7% безазотистых экстрактивных веществ [2]. Предложено много путей утилизации пивной дробины: рекультивация нефтезагрязненной черноземной почвы [2][3][4], экспериментально апробированная в полевых условиях на черноземе в Самарской области [3]; использование в качестве ингредиента в исходном сырье для получения жидкофазных биологически активных средств для растениеводства и земледелия [5]; применение в качестве реагента для обработки буровых растворов [6]; в качестве сырья для получения ксилозы и ксилита [7] для производства молочной кислоты, активированного угля и фенольных кислот [8] при химико-термической обработке для получения топлива [9]. В обзоре [10] рассмотрено применение пивной дробины (brewer'sspentgrain (BSG)) в различных производствах.…”
unclassified